Spray deposition of Cu2ZnSnS4 thin films - Valdes, Matias Hernan (2013)
Thin films of Cu2ZnSnS4 (CZTS) have been deposited on top of glass substrates using spray pyrolysis and aqueous precursors. The substrate temperatures ranged from 325 to 425 ºC. The effect of a thermal treatment in sulfur vapor on the structural, morphological, and optical properties of CZTS films have been studied. X-ray diffractograms revealed the formation of polycrystalline CZTS films, where the crystalline degree increased with substrate temperature and with the use of sulfur during annealing. Raman maps show a homogenous distribution of the CZTS phase along the analyzed surface and a random distribution of a CuXS binary phase. Raman signals attributed to this secondary phase seem to be reduced after sulfurization. Band gap values vary between 1.3 and 1.5 eV. The sulfurization treatment has no significant effect on the composition of the deposits or on the band gap energy value. However, the crystallite size increased after annealing in sulfur. Films deposited at 425 ºC presented a nearly stoichiometric composition, suitable optical properties and p-type conductivity. These materials are suitable for absorbent layers in solar cell fabrication, even in the asdeposited condition.